Perkembangan dan Faktor yang Berhubungan dengan Balita Wasting di Kota Padang: Development of Under-five Wasting Children and Related Factors in Padang City - Desmawati, Desmawati; Sihaloho, Febri Theresia; Utama, Bobby Indra (Amerta Nutrition, 2025)
Background: At the age of under five years, there is rapid physical, cognitive, social, and emotional development, which influences their future abilities. The prevalence of wasting in Indonesia is 7.7%, but it has not received serious attention, so it needs to be explored further. Objectives: This Study aimed to examine the development of under-five wasting children and any associated factors in the Anak Air's Health Center Working Area, Padang City. Methods: It was observational analytical research with a cross-sectional design. The research sample was under-five wasting children aged 12 – 60 months, totaling 118 people taken as respondents. Data on the internal factors of respondents was collected using a validated questionnaire. The development of respondents was examined by using the pre-developmental screening questionnaire. Data was analyzed using chi-square and ordinal logistic regression. Result: This study found that most respondents were under 3 years old, male, had normal birth weight, and had no history of suffering from infectious diseases. A total of 13 (11.1%) of respondents had deviation development, 59 (50%) were doubtful, and only 46 (38.9%) had normal development. Bivariate results showed a significant relationship between age, gender, and infectious diseases with respondents' development (p-value<0.5). There is no significant relationship between birth weight and the respondents’ development (p-value>0.5). Age is the most related factor to the respondents’ development. Conclusion: The conclusion is most respondents have questionable and distorted development, and age is the most related factor. More attention is needed for under-five wasting children so that their development is normal.